Evaluasi Model Queque: Multi Channel, Single Phase Antrian pada Bank Rakyat Indonesia Makassar - Awaluddin, Murtiadi; Sijal, Mutakallim; Aswar, Aswar; Gani, Abdul; Tuarita, Adam (Study of Scientific and Behavioral Management, 2023)
This study aims to determine the implementation of the Queue model: Multi Channel, Single Phase customer queue at Bank Rakyat Indonesia Ahmad Yani Makassar Branch Office. This research is a descriptive research with a quantitative approach. This study uses primary data sources, primary data collects data by means of a direct survey of the queues at Bank Rakyat Indonesia Ahmad Yani Makassar Branch which calculates the number of customers who transact for 5 days from January 9 to January 13 2023 starting at 08.00 -15.00 WITA. The sample of this study is a random sample which is a customer who was queuing at that time. The data processing method in this study is to analyze customers using the Multi Channel, Single Phase (M/M/s) queuing line. The results of the research data show that the busyness of bank queues occurs at 08.00-09.00 WITA, with a percentage of 72.75%, with an average number of customers of 26 people. While the longest waiting time for customers to be served occurs at 08.00-09.00 WITA around 7.365 minutes in the service system.